Design and Performance Prediction of a Compact MmNi4.6Al0.4 based Hydrogen Storage System. (July 2021) - Jana, Sayantan; Muthukumar, P.
Highlights: Two shell and tube type metal hydride (MH) reactor configurations are studied. Hydrogen storage performance is predicted using COMSOL multiphysics 5.3. A 100 kg MH storage system comprising of 4 tube bundle reactor module is proposed. Parametric analysis is performed to study the effect of operating parameters. One MH module can store 307.5 g hydrogen at 30 bar, 298 K absorption condition. Abstract: The present work is focused on the design and numerical prediction of hydrogen storage performance of a compact MmNi4.6 Al0.4 based hydrogen storage unit. Two types of shell and tube reactors capable of holding the same amount of metal alloy are compared for hydriding performance using a 3-D numerical model realized in COMSOL Multiphysics 5.3. The first configuration is an Embedded Cooling Tube (ECT) model where the alloy is contained in the shell and Heat Transfer Fluid (HTF) flows through the tubes; whereas in the second configuration, the alloy is contained in the tubes, which is termed as tube bundle (TB), and HTF flows over the tube bundle inside a shell. The TB configuration showed marginally better initial hydriding rate as compared to the ECT configuration and yielded 1.17 times higher alloy-to-container weight ratio. Based on the TB configuration design methodology, a metal hydride based hydrogen storage unit of 100 kg alloy capacity was proposed, where 4 tube bundle modules of 25 kg alloy capacity each could be arranged in parallel. A parametric study was conducted on the 25 kg reactor module to analyse the effects of various operating parameters viz. supply pressure, HTF temperature and convective heat transfer coefficient on hydrogen storage behaviour. Numerical study predicted that the MH module could store 307.5 g of hydrogen in 600 s, when subjected to 30 bar supply pressure at 298 K HTF temperature, whereas 292.5 g of hydrogen could be discharged at 1 bar, in 1000s, at 303 K HTF temperature.